Oval-sustainability in entrepreneurship - Maryna Pashkevych; Maryna Kharchenko; Nataliia Shishkova (Open Economics, 2018)
Although the sustainable development (SD) is associated with the triple balance of economic, social and environmental areas, we raised a question: whether it is an achievable goal for ordinary business units to develop sustainably. The theoretical research substantiates the contradictory essence of the SD in the context of entrepreneurship. Having employed the method of projection, we offered an advanced definition of the SD for an enterprise. Having applied the theory of the company life-cycle, we obtained stages of the enterprise's SD. The method of typology analysis allowed distinguishing new types of the SD. By means of the cost-benefit analysis, the research reveals OVAL-sustainability as a function of two variables (cost and value).
Keywords: M14; M29; 330; business; enterprise; entrepreneurship; management; Sustainable development